Digital entrepreneurial marketing: A bibliometric analysis reveals an inescapable need of business schools. Issue 2 (July 2022) - Amjad, Tayyab
Abstract: Economic growth and job creation through entrepreneurship/SME development is the key concern globally. On the other hand, marketing failure in nascent graduates who choose to start entrepreneurial careers is a big problem due to the lack of digital/entrepreneurial marketing skills that are required for the survival and growth of SMEs. A wide range of studies suggest that the major reason for lacking such valuable skills is the pedagogical and practical gaps in the marketing education at business schools (BSs) worldwide. To address this practical problem, I follow the pragmatic paradigm, and perform in-depth bibliometric analysis. I identify that digital marketing is actually an essential part of the entrepreneurial marketing, which leads me to introduce the term 'Digital Entrepreneurial Marketing' (DEM). Based on the analysis, I give detailed practical implications to academic authorities at BSs worldwide for the introduction of DEM courses, particularly focusing on SMEs. Further, I show that DEM is practised equally in both developing and developed countries, thus making its learning relevant worldwide. And lastly, I highlight an alarming situation for BSs worldwide regarding their education quality, which needs to be responded timely with the introduction of courses like DEM. Highlights: Based on the bibliometric analysis, it has been demonstrated that digital marketing is an essential part of the entrepreneurial marketing which is highly practiced in SMEs.Thus, the term that best describes the marketing activities of SME entrepreneurs is the 'Digital Entrepreneurial Marketing' (DEM). The analysis also reveals that DEM is practiced abundantly in both developing and developed countries. Teaching DEM at business schools (BSs) would greatly help in overcoming the pressing problem of marketing failure among nascent graduate entrepreneurs in SMEs. Following active learning pedagogies for DEM at BSs, students must be taught how to use social media marketing and its tools on various online platforms; and how to use data and machine learning applications to know and understand the consumer behavior and launch targeted advertisements.